2013
DOI: 10.5489/cuaj.873
|View full text |Cite
|
Sign up to set email alerts
|

Wait times in prostate cancer diagnosis and radiation treatment

Abstract: Introduction: Wait times for cancer diagnosis and treatment area significant concern for Canadians. Men with prostate cancerexperience longer waiting times for diagnosis and treatment thanthose observed for other cancers. Longer waits are associated withboth patient and family psychosocial distress and may be associatedwith worse prognosis.Methods: Men referred for treatment of prostate cancer at a singleCanadian cancer centre were interviewed. The intervals from suspicionto definitive therapy were calculated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…Patients who had biopsies within 4 months of initiation of symptoms were two times likely to be diagnosed early compared to patients who had biopsies after 4 months. This is comparable to a studies conducted in Florida, USA and Toronto, Canada which found that men diagnosed with early stage prostate cancer had a shorter wait time to diagnosis (14). We further found that most patients were lost to follow up while others had succumbed to prostate cancer within two years.…”
Section: Discussionsupporting
confidence: 88%
“…Patients who had biopsies within 4 months of initiation of symptoms were two times likely to be diagnosed early compared to patients who had biopsies after 4 months. This is comparable to a studies conducted in Florida, USA and Toronto, Canada which found that men diagnosed with early stage prostate cancer had a shorter wait time to diagnosis (14). We further found that most patients were lost to follow up while others had succumbed to prostate cancer within two years.…”
Section: Discussionsupporting
confidence: 88%
“…Despite these aspects, the very long waiting times for men with prostate cancer in Sweden as well as the differences between counties are unacceptable and need to be addressed. It is not known whether these long waiting times have a negative impact on outcome, but it has been shown in previous studies that a prolonged wait causes psychological distress to these patients [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have demonstrated that wait times for treatment (for example, between the decision to treat and the start of treatment) continue to be longer for men with pca than for individuals with other cancers in Canada's universal health care system [6][7][8][9][10][11] . Prolonged delays between cancer diagnosis and treatment have been associated with anxiety, stress, and perceived powerlessness for patients and their family members [12][13][14] . Longer wait times might also be associated with poorer prognosis, although the evidence is inconclusive 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged delays between cancer diagnosis and treatment have been associated with anxiety, stress, and perceived powerlessness for patients and their family members [12][13][14] . Longer wait times might also be associated with poorer prognosis, although the evidence is inconclusive 14 . Examination of wait times for cancer care across Canada is therefore an ongoing need.…”
Section: Introductionmentioning
confidence: 99%